Empowering English Teachers: Implementing Flipped Learning in SMP and MTs Muhammadiyah in Banyumas - Furqon, Miftahul; Faisal, Faisal; Pujiyatno, Ambar (PT FORMOSA CENDEKIA GLOBAL, 2024)
The training activity on the application of flipped learning for English teachers of Muhammadiyah Junior High School and MTs in Banyumas aims to improve their teaching skills, especially in learning recon texts. The stages of the activity include preparation, implementation, and evaluation. In the implementation stage, the resource person explained the basic theory of flipped learning in language learning, provided examples of material about recon texts, and guided teachers to prepare materials, including vocabulary, generic structures, simple past tenses, and text examples. Participants showed a positive response to the practice of flipped learning through collaborative and independent writing activities based on picture series. Some supporting factors include the active involvement of participants and relevant materials, while challenges include time constraints and variations in teachers' abilities. The follow-up plan includes advanced training, module development, and strengthening teachers' collaborative strategies.